Numeric Tuning of Surface Plasmon Enhanced Spontaneous Emission Inducted by Nano-Metallic Particle Systems Embedded in GaN-Based LED - Lin, Yi-Zhu; Liu, Duan-Yang; Gao, Jin-Wei (Journal of display technology, 2015)
In this work, spontaneous emission enhancement inducted by surface plasmon on nano-metallic particle systems embedded in GaN-based LED is investigated numerically. The systems under study consist of two nano-Ag balls or cylinders. By numerically tuning geometrical parameters of the system and polarization of the photon emitting source, we investigate the dependence of spontaneous emission enhancement effect on those factors. It is found that the enhancement magnitude level and peak position are subject to geometrical characteristics of the nano-Ag components in different manners for symmetrical and asymmetrical systems respectively. Higher enhancement ratio for a specific wavelength can be obtained by tweaking parameters of asymmetrical system. Polarization dependence of enhancement effect can be utilized to improve performance of bi-color LED.